2014
DOI: 10.1002/2013gl058922
|View full text |Cite
|
Sign up to set email alerts
|

Convective vertical velocity and cloud internal vertical structure: An A‐Train perspective

Abstract: This paper describes a novel use of A-Train observations to estimate vertical velocities for actively growing convective plumes and to relate them to cloud internal vertical structure. Convective vertical velocity is derived from time-delayed (1-2 min) IR measurements from MODIS and IIR. Convective vertical velocities are found to be clustered around 2-4 m/s but the distributions are positively skewed with long tails extending to larger values. Land convection during the 13:30 overpasses has higher vertical ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 25 publications
2
23
0
Order By: Relevance
“…These contrasts in CFTD between land and oceanic deep convective cores are very similar to that between strong and weak convection (sorted by vertical velocity) as reported in Luo et al . []. Hence, CloudSat CPR observations suggest that land convection generates more intense cores than the oceanic counterpart, consistent with direct measurements from cloud‐penetrating aircraft [e.g., LeMone and Zipser , ; Lucas et al ., ] and inference made from analyzing TRMM precipitation radar data [ Liu and Zipser , ; Zipser et al ., ].…”
Section: Regional Variationsmentioning
confidence: 99%
“…These contrasts in CFTD between land and oceanic deep convective cores are very similar to that between strong and weak convection (sorted by vertical velocity) as reported in Luo et al . []. Hence, CloudSat CPR observations suggest that land convection generates more intense cores than the oceanic counterpart, consistent with direct measurements from cloud‐penetrating aircraft [e.g., LeMone and Zipser , ; Lucas et al ., ] and inference made from analyzing TRMM precipitation radar data [ Liu and Zipser , ; Zipser et al ., ].…”
Section: Regional Variationsmentioning
confidence: 99%
“…Luo et al (2014) use time-differenced infrared brightness temperatures to relate cloud top vertical velocities to convective mass transport and precipitation efficiency, two central physical characteristics linking the causes and effects of convective aggregation. They demonstrate that stronger updrafts correlate with higher precipitation echo-tops, increased convective mass fluxes, and heavier rainfall throughout the tropics.…”
Section: Spaceborne Cloud Radar Approachesmentioning
confidence: 99%
“…In this case, the horizontal wind speed is smaller, but the fast cloud evolution is the major issue. Luo et al (2014) and Schumacher et al (2015) reported that tropical DCCs located at altitude between 6 and 8 km typically have an updraft velocity about 2-4 m s −1 . According to this analysis, the comparisons are restricted to | t| < 500 s for the cirrus case, while for the DCC case the threshold is tightened to | t| < 300 s.…”
Section: Data Filtermentioning
confidence: 99%